2002
DOI: 10.1191/0961203302lu256oa
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of acquired activated protein C resistance in patients with systemic lupus erythematosus

Abstract: Antiphospholipid antibodies (aPL) may induce acquired activated protein C resistance (acquired APCR). The role of acquired APCR in patients with systemic lupus erythematosus (SLE) is not well known. To evaluate the prevalence of acquired APCR and its association with clinical manifestations we studied 103 consecutive SLE patients and 103 matched controls. APCR in the undiluted test and after dilution in factor V deficient plasma, factor V Leiden, protein C and S, lupus anticoagulant, and anti-cardiolipin, anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…In 2 previous studies, APC resistance was associated with VTE in children and with ATE in adults, respectively. 23,24 This discrepancy might be due to differences in the applied laboratory tests.…”
Section: Discussionmentioning
confidence: 99%
“…In 2 previous studies, APC resistance was associated with VTE in children and with ATE in adults, respectively. 23,24 This discrepancy might be due to differences in the applied laboratory tests.…”
Section: Discussionmentioning
confidence: 99%
“…One study also suggested that acquired APC resistance could also be associated with pregnancy losses. 8 In conclusion, using a thrombin generation based APC sensitivity assay we have shown that patients with SLE and primary APS displayed a hypercoagulable state characterized by APC resistance. Thrombin generation in antiphospholipid syndrome S Zuily et al…”
Section: Discussionmentioning
confidence: 99%
“…This gene poly- morphism shows a prevalence of 3-6% in Caucasians and in the population of the Indian subcontinent [Muñoz-Rodríguez et al, 2002]. It has been associated with deep venous thrombosis of legs in young female smokers [Capaccio et al, 2007;Görur et al, 2005;Muñoz-Rodríguez et al, 2002;Rosendaal et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…To detect factor V polymorphism, polymerase chain reaction (PCR) amplification and allele-specific oligonucleotide (ASO) hybridization was performed (mDx Factor V Leiden; BioRad, Hercules, Calif., USA) [Thein and Walance, 1986]. The region of the factor V DNA carrying the Leiden mutation (1691 G ] A) was amplified with 2 specific 5 -biotinilated oligonucleotide primers [Muñoz-Rodríguez et al, 2002]. To detect amplified DNA, ASO probes for the wild or the mutant allele of the factor V gene were used.…”
Section: Thrombophilia Studiesmentioning
confidence: 99%